Improved Regeneration, Acclimatization and Shoot Cutting Production of âGebangâ Cassava Derived from Irradiated In Vitro Shoots - Supatmi, Supatmi; Sudarmonowati, Enny (ANNALES BOGORIENSES, 2012)
Gebang is an Indonesian local genotype which has been selected as superior genotype for low amylose Â cassava. Prior to induction of new mutants of this genotype, series of research have been conducted to improve regeneration and acclimatization as well as shoot cuttings production of irradiated in vitro shoots. Four dosage treatments of gamma ray irradiation i.e. those of at 0; 0.2; 1.0; 1.5; 2.0 krad were applied to 32 in vitro shoots multiplied from apical shoots of plants in the field. The highest multiplication rate and acclimatized shoots were obtained from shoots irradiated with 0.2 krad multiplied on various level of BAP added on MS medium and resulted that MS supplemented with 1 mg/L BAP was the best medium. The phenotypic variation was observed in shoots irradiated with 1.0; 1.5 and 2.0 krad while the ones irradiated with 0.2 krad performed normal appearances. Subsequent production of propagated young stem cuttings called âratooning systemâ decreased after the second cycle of propagation especially in the survival rate of the ones irradiated with 0.2 krad. The findings lead to the opportunity to produce cassava propagules derived from irradiated in vitro culture at a higher amount using Gebang genotype as a model.Keywords: cassava Gebang, irradiated shoot, young stem cutting/ratooning , acclimatization, in vitro.